Implikasi Declaration of Conduct Laut Tiongkok Selatan Tahun 2002 Terhadap Proses Penyelesaian Sengketa - Haryanto, Agus; Bainus, Arry (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2017)
Overlapping sovereignty in the South China Sea (SCS) has been serious problem since the 1970s. A formal agreement was reached between China and ASEAN is Declaration of Conduct (DoC) that signed in 2002. However, the existence of the DoC has not yet been able to defuse the dispute in the SCS. This paper will elaborate the DoC weaknesses that have a low bonds, precision and delegation. Thus, it is understandable if the DoC was not able to organize parties - disputants. Therefore the parties need to have a Code of Conduct (CoC) to follow up the DoC.